Functional and Structural Insights of the Zinc-Finger HIT protein family members Involved in Box C/D snoRNP Biogenesis. Issue 11 (5th June 2016) - Bragantini, Benoit; Tiotiu, Decebal; Rothé, Benjamin; Saliou, Jean-Michel; Marty, Hélène; Cianférani, Sarah; Charpentier, Bruno; Quinternet, Marc; Manival, Xavier
Abstract: Zf–HIT family members share the zf–HIT domain (ZHD), which is characterized by a fold in "treble-clef" through interleaved CCCC and CCHC ZnF motifs that both bind a zinc atom. Six proteins containing ZHD are present in human and three in yeast proteome, all belonging to multimodular RNA/protein complexes involved in gene regulation, chromatin remodeling, and snoRNP assembly. An interesting characteristic of the cellular complexes that ensure these functions is the presence of the RuvBL1/2/Rvb1/2 ATPases closely linked with zf–HIT proteins. Human ZNHIT6/BCD1 and its counterpart in yeast Bcd1p were previously characterized as assembly factors of the box C/D snoRNPs. Our data reveal that the ZHD of Bcd1p is necessary but not sufficient for yeast growth and that the motif has no direct RNA-binding capacity but helps Bcd1p maintain the box C/D snoRNAs level in steady state. However, we demonstrated that Bcd1p interacts nonspecifically with RNAs depending on their length. Interestingly, the ZHD of Bcd1p is functionally interchangeable with that of Hit1p, another box C/D snoRNP assembly factor belonging to the zf–HIT family. This prompted us to use NMR to solve the 3D structures of ZHD from yeast Bcd1p and Hit1p to highlight the structural similarity in the zf–HIT family. We identified structural features associated with the requirement of Hit1p and Bcd1p ZHD for cell growth and box C/D snoRNA stability under heat stress. Altogether, our data suggest an important role of ZHD could be to maintain functional folding to the rest of the protein, especially under heat stress conditions. Graphical Abstract: Highlights: ZHD of Bcd1p contributes to the steady-state level of the box C/D snoRNAs and is essential for cellular viability. The 3D solution structure of ZHDs of Bcd1p and Hit1p was determined by NMR. Bcd1p ZDH is functionally interchangeable with Hit1p ZDH, another box C/D snoRNP assembly factor. Mutation of the ZnF2 motif in the ZHD of Bcd1p induces a heat-sensitive phenotype in yeast. The Bcd1p ZHD is a functional fold stabilizer.